2020
DOI: 10.20944/preprints202003.0378.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Treatment: Close to a Cure? – A Rapid Review of Pharmacotherapies for the Novel Coronavirus

Abstract: Currently, there is no specific treatment for COVID-19 proven by clinical trials. WHO and CDC guidelines therefore endorse supportive care only. However, frontline clinicians have been applying several virus-based and host-based therapeutics in order to combat SARS-CoV-2. Medications from COVID-19 case reports, observational studies and the COVID-19 Treatment Guideline issued by the China's National Health Commission (7th edition published March 3rd, 2020. Edited translation attached) are evaluated in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
0
27
0
1
Order By: Relevance
“…Many FDA-approved and investigational anti-viral drugs, alone or in combination, used in the past against SARS and MERS, are being investigated against COVID-19. However, even with massive efforts, no specific antiviral treatment or vaccination for COVID-19 is yet available [ 9 , 10 ]. Hence, there is an urgent need to combat this highly contagious disease, which requires a clear understanding of disease pathology and critical strategies in identifying new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Many FDA-approved and investigational anti-viral drugs, alone or in combination, used in the past against SARS and MERS, are being investigated against COVID-19. However, even with massive efforts, no specific antiviral treatment or vaccination for COVID-19 is yet available [ 9 , 10 ]. Hence, there is an urgent need to combat this highly contagious disease, which requires a clear understanding of disease pathology and critical strategies in identifying new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is caused by infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which has spread around the globe and is causing an ongoing severe pandemic with 11,874,226 confirmed cases and 545,481 deaths worldwide that have been reported to the World Health Organization (WHO) as of July 9, 2020 ( https://www.who.int/emergencies/diseases/novel-coronavirus-2019 ). To date, there is still no known approved curative drug therapy specific for COVID-19, especially for patients with the severe and critical forms [ 1 ]. However, chloroquine phosphate and its derivative hydroxychloroquine, which have been used for decades in the treatment and prevention of malaria and chronic inflammatory diseases such as rheumatoid arthritis and systemic lupus erythematosus, were discovered to have a high inhibitory potency against SARS-CoV-2 infection in vitro [ 2 5 ] and favorable clinical and virologic benefits in COVID-19 patients [ 6 10 ], and they have emerged as important therapies for COVID-19 in several countries, including China, France, USA, and India, although the mechanisms of their anti-COVID-19 effects remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Arbidol reduces the virus's infectivity by clinging to the hemagglutinin and preventing the virus from entering the cell (7). In a study of 69 diseases in China, Arbidol has been shown to reduce the mortality rate and increase healing (8).…”
Section: Introductionmentioning
confidence: 99%